Bevacizumab plus capecitabine and cisplatin in Chinese patients with inoperable locally advanced or metastatic gastric or gastroesophageal junction cancer: randomized, double-blind, phase III study (AVATAR study) - Shen, Lin; Li, Jin; Xu, Jianming; Pan, Hongming; Dai, Guanghai; Qin, Shukui; Wang, Liwei; Wang, Jinwan; Yang, Zhenzhou; Shu, Yongqian; Xu, Ruihua; Chen, Lei; et al. (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2015)
Background In the AVAGAST study, fluoropyrimidine and cisplatin plus bevacizumab did not significantly improve overall survival (OS) versus fluoropyrimidine and cisplatin plus placebo in patients with advanced gastric cancer. Geographic differences in efficacy were observed in AVAGAST, but the study only included 12 Chinese patients. AVATAR, a study similar in design to AVAGAST, was a randomized, double-blind, phase III study conducted in Chinese patients with advanced gastric cancer. Methods Patients more than 18 years of age with gastric adenocarcinoma were randomized 1:1 to capecitabine–cisplatin plus either bevacizumab or placebo. The primary endpoint was OS; secondary endpoints included progression-free survival (PFS) and safety. Results In total, 202 patients were included (placebo n = 102; bevacizumab n = 100). Baseline characteristics were well balanced. The primary analysis result did not show a difference in OS for the bevacizumab arm compared to the placebo arm [hazard ratio, 1.11 (95 % CI, 0.79–1.56); P = 0.5567]. Median PFS was also similar in both arms. Bevacizumab plus capecitabine–cisplatin was well tolerated. Grade 3–5 adverse events (AEs) occurred in 60 % of bevacizumab-treated and 68 % of placebo-treated patients, respectively. Grade 3–5 AEs of special interest with bevacizumab occurred in 8 % of bevacizumab-treated patients and 15 % of placebo-treated patients, mainly grade 3–5 hemorrhage (bevacizumab 4 %, placebo 12 %). Conclusions Addition of bevacizumab to capecitabine–cisplatin in Chinese patients with advanced gastric cancer did not improve outcomes in AVATAR. There was no difference in OS between the two arms and PFS was similar in both arms. Safety findings were as previously experienced with bevacizumab, including AVAGAST; no new safety signals were reported.